2023
DOI: 10.3390/f14081566
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Analysis and Regression Modeling of SPAD Measurements in Leaves of Three Mangrove Species

Huazhe Li,
Lijuan Cui,
Zhiguo Dou
et al.

Abstract: Mangroves have important roles in regulating climate change, and in reducing the impact of wind and waves. Analysis of the chlorophyll content of mangroves is important for monitoring their health, and their conservation and management. Thus, this study aimed to apply four regression models, eXtreme Gradient Boosting (XGBoost), Random Forest (RF), Partial Least Squares (PLS) and Adaptive Boosting (AdaBoost), to study the inversion of Soil Plant Analysis Development (SPAD) values obtained from near-ground hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…For example, for mangrove plants, a report showed that the SPAD reading ranges for Avicennia marina, Rhizophora stylosa, Bruguiera gymnorhiza, and Aegiceras corniculatum were 41. 50-56.8, 70.40-80.10, 52.80-69.90, and 42.30-73.60, respectively [42], while another study recorded that the average values for Bruguiera sexangula, Ceriops tagal, and Rhizophora apiculata were 58.60, 61.56, and 66.57, respectively [23]. Intrinsic plant factors (such as developmental stages) and external factors (such as light intensity) can both affect SPAD values.…”
Section: Spad Value As a Good Predictor For Photosynthetic Pigment Co...mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, for mangrove plants, a report showed that the SPAD reading ranges for Avicennia marina, Rhizophora stylosa, Bruguiera gymnorhiza, and Aegiceras corniculatum were 41. 50-56.8, 70.40-80.10, 52.80-69.90, and 42.30-73.60, respectively [42], while another study recorded that the average values for Bruguiera sexangula, Ceriops tagal, and Rhizophora apiculata were 58.60, 61.56, and 66.57, respectively [23]. Intrinsic plant factors (such as developmental stages) and external factors (such as light intensity) can both affect SPAD values.…”
Section: Spad Value As a Good Predictor For Photosynthetic Pigment Co...mentioning
confidence: 98%
“…One of them is a CIE L*a*b* system, such as an NR20XE Precision Colorimeter (Shenzhen ThreeNH Technology, Shenzhen, China) [18], a Hand-held Color Analyzer (CM-2500D, Konica Minolta, Osaka, Japan) [19], or a Minolta Chroma Meter (Model CR200/300, Minolta, Ramsey, NJ, USA) [20]. Another is a portable Chl meter (SPAD-502Plus, Minolta Camera Co., Osaka, Japan) [21][22][23]. The SPAD-502 has been widely used for assessing or diagnosing a plant's nitrogen status [24][25][26], health status [27], pest and disease stress [28], leaf senescence [29], and coloration effects [30].…”
Section: Introductionmentioning
confidence: 99%